Diagnostic Applications of Ultrasonography in Myofascial Trigger Points: A Scoping Review and Critical Appraisal of Literature. (November 2022) - Elbarbary, Mohamed; Sgro, Adam; Goldberg, Michael; Tenenbaum, Howard; Azarpazhooh, Amir
Objective: Myofascial trigger points (MTrPs) are pathognomonic of myofascial pain syndrome. The detection ability of MTrPs via ultrasonography is underreported and the characteristics of MTrPs are not sufficiently standardized. The objective was to summarize the characteristics and diagnostic abilities of ultrasonography for MTrP investigations. Materials and Methods: A multi-database, and bibliography hand-search was implemented. Studies of ≥10 patients, published after 1980, appraising ultrasonography as a diagnostic aid for myofascial pain syndrome were included. The Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool was used to evaluate the diagnostic accuracy of the included studies. Results: Six cross-sectional studies met the inclusion criteria. The back and trapezius muscles were the most studied locations. The diagnostic studies were of low-medium risk of bias. The studies reported a large range of diagnostic metrics (accuracy 58%–100%, sensitivity 33%–91%, specificity 75%–100%, positive predictive value 91%–100%, negative predictive value 47%–97%, positive likelihood ratio 3.6, and negative likelihood ratio 0.12–0.67). Conclusion: This review found low-medium risk of bias evidence in support of ultrasonography for MTrP investigations. The clinical studies identified in the scoping review used gray-scale ultrasound equipment systems with a 5 to 14 MHz transducer to diagnose MTrPs and the local twitch response, and MTrPs were visualized mostly as hypoechoic nodules.